Effect of age, stress and protein supply on plasma amino acids during continuous enteral nutrition; a pragmatic study in rats. Issue 6 (June 2021) - Ventura, G.; Le Plenier, S.; Neveux, N.; Sarfati, G.; Cynober, L.; Raynaud-Simon, A.; De Bandt, J.P.
Summary: Background & aims: As life expectancy increases, an increasing older population may require surgery with perioperative nutritional management. While little is known about the combined effect of age and stress on amino acid metabolism during enteral nutrition, we hypothesized that blood amino acid bioavailability may be influenced not only by the characteristics of the ingested protein but also by intestinal ageing and splanchnic sequestration of amino acids. Plasma amino acid kinetics were thus evaluated in aged and adult rats receiving continuous enteral nutrition before and after standardized surgical stress. Methods: Sixteen 5-month-old and sixteen 21-month-old male rats were used. After a gastrostomy, the insertion of a jugular vein catheter and a one-week recovery, the animals were enterally fed with commercially available formulas containing whole milk proteins or a whey hydrolysate for 24 h before (healthy state) and 18 h after a standardized laparotomy (surgical stress). Data were analyzed by 3-factor ANOVA. Results: In all rats, enteral nutrition was associated with a marked increase in plasma alanine, threonine, lysine and proline (+50 to +150 μmol/L; p < 0.001), and a decrease in glycine (≈-80 μmol/L; p < 0.01). For most amino acids, their availability depended first on the amino acid composition of each protein and second on surgical stress. Aging was only associated with higher tyrosine and threonine availability (p < 0.001). There was only limited statistical interaction between age and surgical stress. Conclusion: In rats, plasma amino acid availability during continuous enteral nutrition is determined by the nature of the protein source and the occurrence of stress. The effects of aging on plasma amino acid availability seem very limited. Commonly used formulas therefore appear to be as suitable for elderly patients as for adult patients.